Seasonal discrepancies in peroxyacetyl nitrate (PAN) and its correlation with ozone and PM2.5: Effects of regional transport from circumjacent industrial cities - M. Sun; Y. Zhou; Y. Wang; Zheng, X.; J. Cui; D. Zhang; J. Zhang; Zhang, R. (Science of the Total Environment, 2021)
Peroxyacetyl nitrate (PAN) is the most important reservoir of nitrogen oxides, with effects on atmospheric oxidation capacity and regional nitrogen distribution. The first yearlong observational study of PAN was conducted from September 2018 to August 2019 at a suburban site and an urban site in Zhengzhou, Henan Province, central China. Compared with studies over the past two decades, summer PAN pollution at the suburban site and winter PAN pollution at both sites were more significant, with annual average concentrations of 1.96 ± 1.44 and 2.01 ± 1.59 ppbv, respectively. Seasonal PAN discrepancies between the urban and suburban areas were analyzed in detail. Active PAN formation, regional transport, photochemical precursors, and PAN lifetime played key roles during seasons with elevated PAN (winter and spring). According to the results of cluster analysis and potential source contribution function analysis, during the cold months, short-distance air mass transport from the east, south, and southeast of Henan Province and southern Hebei Province increased PAN pollution in urban Zhengzhou. PAN source areas were located in circumjacent industrial cities surrounding Zhengzhou except in the northeastern direction. Based on the relationships between pollutant concentrations, wind speed, and wind direction, a strong positive correlation between PAN and PM2.5 (and O3) existed in winter due to their joint transport. A slow-moving, low-height air mass passed through surrounding industrial cities before reaching the study area, carrying both pollutants and leading to strong consistency between PAN and O3 levels. The long-term PAN characteristics described in this study will help clarify the causes of regional air pollution in inland city agglomerations. Moreover, the PAN correlations and joint transport of PAN and PM2.5 (or O3) support the use of PAN as an indicator of air pollution introduced from surrounding industrial areas. © 2021 Elsevier B.V.
Keywords: Agglomeration; Air mass; air pollution; atmospheric pollution; China; Cluster Analysis; concentration (composition); fine particulate matter; Henan; Henan Province; Indicator indicator; Industrial city; Industrial urban agglomeration; nitrate pollution; Nitrates; Nitrogen oxides; ozone; particulate matter; peroxyacetyl nitrate; Peroxyacetyl nitrates; PM$-2.5$; Regional transport; Suburban sites; transport process; Urban growth; urban region; Urban transportation; Wind; Zhengzhou